Dopamine neuron loss by selective deletion of autophagy-related gene 5 is not exacerbated by MPTP toxicity in midbrain. (14th May 2018) - Ren, Yan-Hua; Niu, Xue-Yuan; Huang, Hou-Ju; Hao, Xiao-Di; Wang, Peng-Xiang; Chi, Yi-Li; Ding, Yu-Qiang; Liao, Min
Highlights: Conditional knockout of Atg5 reduced midbrain dopamine neurons. MPTP-induced neural toxicity was not observed in Atg5 knockout mice. Atg5-involved autophagy is likely necessary for midbrain dopamine neuron survival. Atg5-involved autophagy is likely involved in MPTP-induced neuronal degeneration. Abstract: Parkinson's disease (PD) is a progressive neurological disease, one of the pathological characteristics is a gradual loss of midbrain dopaminergic (mDA) neurons in the substantia nigra pars compacta (SNpc). In animals, PD-like symptoms can be induced by genetic mutations or by neurotoxins such as 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP). It has been reported that deletion of autophagy-related gene 5 (Atg5) in the brain can disrupt neural function and is accompanied by the accumulation of cytoplasmic inclusions. However, the exact role of autophagy in PD etiology has not fully been asserted. In this study, we used tyrosine hydroxylase (TH)-Cre mice to generate conditional knockouts (CKO) with the specific deletion of Atg5 in mDA neurons, and found that adult Atg5 CKO mice contained ubiquitin- and p62-positive inclusions and fewer TH-positive mDA neurons compared with wild-type controls. Interestingly, MPTP-induced loss of mDA neurons was not observed in Atg5 CKO mice. Thus, Atg5-associated autophagy is required for the survival of mDA neurons, and may be involved in MPTP-induced neuronal degeneration.